Where are the Librarians?: The Roving Reference Experience of DLSU Libraries - Yap, Joseph Marmol; Cajes, May Laureno (Information World, 2016)
The roving reference concept is relatively new in the Philippines. In 2012, the De La Salle University (DLSU) Libraries shared in its OCLC report entitled “Reference and Information Services in Selected Philippine Academic Libraries: Trends and Future Prospects” that DLSU will be introducing roving reference as part of the services of the DLSU Libraries. RIA or the Roving Information Assistant was finally launched in November 2013 and was pilot tested in July 2014. RIA allows the library staff to engage further with patrons, to expand information assistance, and to create a higher level of customer service in reference transactions. The presence of the librarians is more visible as they roam throughout the spheres of the library. This evaluative research seeks to determine if the objectives of RIA was fulfilled. Online evaluation forms were used to solicit feedback from both the users and the librarians. This paper shares the reference transaction experiences and results of the roving reference service of the De La Salle University Libraries.